A Systematic Review of Individuals’ Acceptance of IOT-based Technologies - Alkawsi, Gamal Abdulnaser; Bte. Ali, Nor’ashikin (International Journal of Engineering and Technology, 2018)
This paper primarily aims to provide a systematic review of factors influencing the individualsâ€™ acceptance of Internet of things (IoT). There are numerous studies in literature that examine factors affecting technology acceptance.Â However, the studies on the review for acceptance of Internet of Things is limited.Â Â This study conducted a review and analysis of 32 articles from academic journals and conference proceedings published about the adoption, acceptance and diffusion of IoT. According to the review outcome, there are increasing numbers of studies that have been conducted in the IoT acceptance among individuals hailing from various points of view, with different factors affecting such viewpoints. Nevertheless, it was also noted that a theoretical, methodological and empirical study has yet to be carried out in the field to determine the factors related to the context of its application. The findings also led the author to recommend more future theoretical, methodological and empirical research to be conducted on the topic.